Increased risk of nonalcoholic fatty liver disease in patients with coeliac disease on a gluten‐free diet: beyond traditional metabolic factors. Issue 5 (8th July 2018) - Tovoli, F.; Negrini, G.; Farì, R.; Guidetti, E.; Faggiano, C.; Napoli, L.; Bolondi, L.; Granito, A.
Summary: Background: A gluten‐free diet (GFD) is known to be associated with altered macronutrient intake and metabolic syndrome. Nonalcoholic fatty liver disease (NAFLD) is the hepatic hallmark of metabolic syndrome. The risk of NAFLD in patients with coeliac disease (CD) adhering to a GFD remains to be fully investigated; in particular, data from real‐life clinical settings are lacking. Aim: To assess the prevalence and relative risk of NAFLD in CD patients treated with a GFD. Methods: Case–control study, with prospective enrolment of CD outpatients following a GFD and controls. Patients were matched for demographic characteristics (age and gender) and metabolic risk factors (overweight, diabetes mellitus, total cholesterol, and triglycerides) using a 1:1 ratio. NAFLD was diagnosed according to the European Association for the Study of the Liver criteria. Results: 202 CD patients and 202 controls were compared. The raw prevalence of NAFLD was 34.7% and 21.8% in the CD and control group, respectively ( P = 0.006). Binary logistic regression confirmed an increased risk of NAFLD in the CD group (adjusted odds ratio = 2.90, 95% confidence interval: 1.64‐5.15, P < 0.001). Additionally, the relative risk for NAFLD was notably higher in non‐overweight CD patients (adjusted odds ratio = 5.71, 95% confidence interval: 2.30‐14.19, P < 0.001). Conclusions: More than one‐third of CD patients adhering to a GFD had concurrent NAFLD, accounting for a three‐fold increased risk compared to the general population. Dietary advice provided using a patient‐tailored approach should assist CD patients with NAFLD in achieving an appropriate nutritional intake whilst reducing the risk of long‐term liver‐related events.